Comparison of ball-and-racket impact force in two-handed backhand stroke stances for different-skill-level tennis players - Lo, K.-C.; Hsieh, Y.-C. (Journal of Sports Science & Medicine, 2016)
This study compared the kinetic roles of the upper extremities in racket impact force generation between the open stance (OS) and square stance (SS) for tennis players with different skill levels in two-handed backhand strokes. Twelve male tennis players were divided into an advanced group (AG) (L3-L2 skill level) and intermediate group (IG) (L7-L6 skill level), and their data were used in a three-dimensional kinetic analysis. Their motions were captured using 21 reflective markers attached to anatomic landmarks for two-handed backhand stroke motion data collection. During the acceleration phase, significant differences were not observed between both stances, but they were observed between the groups with different skill levels for the force of the upper extremities (p = 0.027). The joint forces were significantly lower in the AG than in the IG. Players performing the SS had significantly larger pronation and supination of the wrist joint moment than those in the OS (p = 0.032) during the acceleration phase, irrespective of the playing level. Higher internal rotation moment after impact was observed at each joint, particularly among young intermediate tennis players, regardless of their stance. The AG demonstrated a higher joint force and moment at every joint compared with the IG at impact. Moreover, the AG demonstrated superior stroke efficiency and effectively reduced joint moment after impact and sports injury.